Leyendo el tejido social Análisis discursivo y retórica cultural en el sur global - Valdivia, Pablo; Del Valle, Carlos (University of Groningen Press, 2020)
The contemporary state of affairs, however, is way too complex to presuppose that a simple formula will be enough to synthesize all its multiple facets. The fact that both our institutions and our mental life are regulated by communication is more and more evident. It is also clear that human history should submit itself to a democratic consensus, and that contemporary societies have to proclaim themselves democratic, pretending many times they are following a consensus that must be the kernel of collective and of individual development. This consensus, however, is itself also being submitted to an all-encompassing social experiment. Such an experiment is permanently looking for new laws and new accomplishments, because in complying with the scientific model, it presupposes that laws previously valid, and previous social accomplishments no longer apply because social life is in need of being reinvented and people should live in harmony the new laws. The individuals are therefore entangled in this continuous reconfiguration of their institutions and of themselves. They are nolens volens obliged to judge this perpetual renewal of their social tissue in order to secure their own personal life. This book is an answer to the now globally widespread need of judgment by everyone of the results of this continuous reconfiguration, and although it does not claim any final conclusion, it sums up many important views about our time, coming from human and social that should be an important contribution to the construction a humanity worth living.